Intracavity-Pumped, Mid-Infrared Tandem Optical Parametric Oscillator Based on BaGa4Se7 Crystal - Yixin He; Degang Xu; Jiyong Yao; Yuye Wang; Yangwu Guo; Xianli Zhu; Chao Yan; Longhuang Tang; Jining Li; Kai Zhong; Yicheng Wu; Jianquan Yao (IEEE Photonics Journal, 2019)
We have demonstrated a tunable mid-infrared tandem optical parametric oscillator (OPO) based on BaGa4Se7 (BGSe) crystal, which was intracavity-pumped by the tunable signal wave at ∼1 μm generated from a KTiOPO4-OPO (KTP-OPO) in doubly-resonant oscillator (DRO) configuration. Wavelength tuning of the mid-infrared tandem OPO was realized by tuning the pump wavelength at the fixed phase matching angle to reduce the effects of beam cutting and Fresnel reflection loss. Together with pump-tuning method, angle-tuning method was supplied to extend tuning range. A tuning range of 4.1–4.5 μm was obtained with just 5 individual phase matching angles of the BGSe crystal. The maximum output energy of 1.92 mJ/pulse was obtained at 4.26 μm with an estimated slope efficiency of 9.5%.